Framework for Life Cycle Assessment (LCA) Based Environmental Decision Making During the Conceptual Design Phase for Commercial Buildings. (2015) - Means, Peter; Guggemos, Angela
Abstract: Introduction: In the U.S., about 50% of total CO2 emissions stem from the built environment (e.g., building construction, operation [heating, lighting, cooling], and end-of-life) (EPA 2012). Improving the performance and efficiency of the built environment offers the largest and least cost GHG mitigation option of any sector of the global economy (IPCC 2007). Science-based Life Cycle Assessment (LCA) methods are increasingly being used to analyse the environmental impact of construction materials and products. Objectives: This paper presents a framework for LCA-based environmental decision making for commercial buildings at the conceptual design phase, compares it to the currently available LCA tools and data bases, and identifies the "next steps" in developing a comprehensive LCA standard for assessing whole building life cycles to support environmental decision making in design and construction. Methodology/approach: 1) CSU/AIA conducted focus groups in 8 US cities to explore actual and potential use of LCA in decision making by architects; 2) A framework created based on feedback from focus groups, 3) The framework was compared to existing LCA tools and databases, 4) Gaps were identified for next stages in developing an LCA-based environmental decision-making tool for conceptual design. Findings and contributions: 1) Current LCA tools are balkanized and usually address only one life cycle stage, material or system in a building. 2) LCA-related databases normally only address materials and product; they do not address construction activities or building operations. 3) LCA tools and databases generally require a completely separate activity, data input and expertise; they are not integrated into routinely used architecture, engineering, and construction (AEC) tools, methods or best practices. 4) LCA based decision-making will not become an AEC best practice until it is fully integrated, comprehensive, standardized, affordable, and demanded by customers and municipalities.